2017
DOI: 10.18520/cs/v112/i06/1208-1218
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Snow Accumulation on Samudra Tapu Glacier, Western Himalaya Using Airborne Ground Penetrating Radar

Abstract: In this study an airborne ground penetrating radar (GPR) is used to estimate spatial distribution of snow accumulation in the Samudra Tapu glacier (the Great Himalayan Range), Western Himalaya, India. An impulse radar system with 350 MHz antenna was mounted on a helicopter for the estimation of snow depth. The dielectric properties of snow were measured at a representative site (Patseo Observatory) using a snow fork to calibrate GPR data. The snow depths estimated from GPR signal were found to be in good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…Snow depth measurements between 4700 and 5200 m asl that were conducted in May show that 1.4-1.6 m of snow was accumulated. A recent study by [72] has also observed a similar average accumulated SWE of 0.624 m and 0.496 m during March of 2009 and 2010 over the Samudra Tapu Glacier. Therefore, the ice melt in three seasons suggests the role of snow cover and temperature gradient between the elevations, where the ice surface at lower elevation gets exposed early when compared to that of snow-covered higher elevation.…”
Section: Seasonal Variability In Surface Meltingsupporting
confidence: 54%
“…Snow depth measurements between 4700 and 5200 m asl that were conducted in May show that 1.4-1.6 m of snow was accumulated. A recent study by [72] has also observed a similar average accumulated SWE of 0.624 m and 0.496 m during March of 2009 and 2010 over the Samudra Tapu Glacier. Therefore, the ice melt in three seasons suggests the role of snow cover and temperature gradient between the elevations, where the ice surface at lower elevation gets exposed early when compared to that of snow-covered higher elevation.…”
Section: Seasonal Variability In Surface Meltingsupporting
confidence: 54%
“…The transmission velocity is the most critical parameter for estimating snowpack thickness. Because of the limited measurement time window in so-called 'death zone', we did not measure common midpoint data to evaluate the transmission velocity of radar waves inside the snowpack at the Mount Everest t. In general, the transmission velocity in snow ranges from 0.20 m/ns to 0.27 m/ns, which depend on snow properties (Fortin and Fortier, 2001;Singh et al, 2017). A transmission velocity of 0.23 m/ns was obtained in a snowpack according to radar measurements with a steel stake (40 cm in length and 2 cm in diameter) that was buried in snowpack at elevations of 6500 m and 7028 m in 2005 (Sun et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…4A), it is clear that the antennae used for investigating the narrower snow (and crevasses) was less appropriate and only allowed for locating the crevasses along the bedrock profile (Fig. 4B) without allowing a detailed view of their inner structures as was the case with more dedicated GPR studies (e.g., Eder et al, 2008;Singh et al, 2013). Higher frequencies (ideally from a 500-Mhz antenna) should allow for more details in the structure provided.…”
Section: Detailing the Glacial Contextmentioning
confidence: 99%